Trust, Mistrust and Distrust: A Gendered Perspective on Meanings and Measurements - Bunting, Hannah; Gaskell, Jennifer; Stoker, Gerry (Frontiers in Political Science, 2021)
Recent work has emphasised the need for greater nuance in qualifying both the presence and absence of political trust in different political systems. The concept of trust may thus be more effectively perceived and analysed as a family with trust, mistrust, and distrust as its members. Expanding to a family of trust means that new ways of capturing these attitudes in empirical survey work may be needed and a way of critically driving that exploration is to investigate how gender influences how they are understood. In this paper, we use insights from focus group discussions on a series of newly designed trust, mistrust and distrust questions to identify: 1) how citizens perceive these different concepts and 2) how gendered these perceptions are. We then draw on new survey data gathered through the TrustGov project to test how the focus group findings impact survey responses and thus identify: 3) which survey questions are more likely to effectively measure the three concepts. We show that the differences highlighted in our qualitative work underscore the need to develop a more systematic mixed methods research agenda on both the expanded family of political trust and gender. We emphasise that global comparative work to capture diverse gender effects across different political systems are the necessary next steps for the field.